Una experiencia de trabajo con un grupo de adolescentes con habilidades diferentes - Hurtado Alva, Graciela V. (2006)
This article recounts working experience with a group of adolescents in a week- end program. where a space is given in order to share each other’s by generating a reference group which helps them develop independence and affection. Working with the family is also considered to support the process.